(3COYjI Yf GdQShd Udi Gddg Ydjg hSdes - (3eLghds
(3ChdgG (B:s
(3fGbU GdChd, hChdg(B: (3GdSdGe CTGQ Ydi CHj HJQc GdNQhL hYQag Cf gh NQL haGQb GdeOjfI eG jchf Edjg eUjQs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3hdG JLGRfj HGdGSJMbGb hdcf HQMeJc GdJj hSYJ cd TjA jG PG GdLdGd hGdEcQGe Udi Ydi eMeO hBds
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs